The comprehensive 360° model of research: its foundations and exemplary application in spinal cord injury - Sara Rubinelli; Jerome Bickenbach; James Middleton; Ian Cameron; Carla Sabariego; Gerold Stucki (Journal of Rehabilitation Medicine)
Objective: This paper introduces the “360° Model of Research”, a novel framework designed to prioritize functioning as a primary health indicator, particularly for individuals living with health conditions. The goal is to promote this model as a comprehensive, person-centred, and interdisciplinary approach to health research, moving beyond the traditional siloed and disease-based methodologies.